PHACTR-1 (Phosphatase and Actin Regulator 1) Deficiency in Either Endothelial or Smooth Muscle Cells Does Not Predispose Mice to Nonatherosclerotic Arteriopathies in 3 Transgenic Mice. Issue 5 (7th April 2022) - Rubin, Sébastien; Bougaran, Pauline; Martin, Soizic; Abelanet, Alice; Delobel, Valentin; Pernot, Mathieu; Jeanningros, Sylvie; Bats, Marie-Lise; Combe, Christian; Dufourcq, Pascale; Debette, Stéphanie; Couffinhal, Thierry; et al.
Abstract : Background: Genome-wide association studies have revealed robust associations of common genetic polymorphisms in an intron of the PHACTR-1 (phosphatase and actin regulator 1) gene (chr6p24), with cervical artery dissection, spontaneous coronary artery dissection, and fibromuscular dysplasia. The aim was to assess its role in the pathogenesis of cervical artery dissection or fibromuscular dysplasia. Methods: Using various tissue-specific Cre-driver mouse lines, Phactr1 was deleted either in endothelial cells using 2 tissue-specific Cre-driver (PDGFB [platelet-derived growth factor B]-Cre ERT2 mice and Tie2 [tyrosine kinase with immunoglobulin and EGF homology domains]-Cre) and smooth muscle cells (smooth muscle actin-Cre ERT2 ) with a third tissue-specific Cre-driver. Results: To test the efficacy of the Phactr1 deletion after cre-induction, we confirmed first, a decrease in Phactr1 transcription and Phactr1 expression in endothelial cell and smooth muscle cell isolated from Phactr1 iPDGFB and Phactr1 iSMA mice. Irrespective to the tissue or the duration of the deletion, mice did not spontaneously display pathological phenotype or vascular impairment: mouse survival, growth, blood pressure, large vessel morphology, or actin organization were not different in knockout mice than their comparatives littermates. Challenging vascular function and repair either by angiotensin II–induced hypertension or limb ischemia did not lead to vascular morphology or function impairment in Phactr1-deleted mice. Similarly, there were no more consequences of Phactr1 deletion during embryogenesis in endothelial cells. Conclusions: Loss of PHACTR-1 function in the cells involved in vascular physiology does not appear to induce a pathological vascular phenotype. The in vivo effect of the intronic variation described in genome-wide association studies is unlikely to involve downregulation in PHACTR-1 expression.